Preparation and characteristics of sucrose-resistant emulsions and their application in soft candies with low sugar and high lutein contents and strong antioxidant activity. (August 2022) - Pan, Li-Hua; Wu, Cui-Ling; Luo, Shui-Zhong; Luo, Jian-Ping; Zheng, Zhi; Jiang, Shao-Tong; Zhao, Yan-Yan; Zhong, Xi-Yang
Abstract: Soft candies are popular confections but contain high-sugar and low-functional ingredients. The inclusion of xanthan gum (XG, 0.2–0.5%) in a water-in-oil emulsion stabilized by tea polyphenol palmitate (TPP) particles made structured lutein-loaded emulsions suitable for high-sugar foods. With the increase in XG concentration, the droplet size of the lutein-loaded emulsion decreased, but the lutein loading capacity, G′, G″, and apparent viscosity increased. The G′, G″, G* and η* values of the most desirable emulsion stabilized by 2.5% TPP particles and 0.5% XG were reduced, but tanα increased when 0.25–1.00 g/mL sucrose was added; however, the emulsion remained stable based on the droplet size and zeta potential, suggesting that the lutein-loaded emulsion was sucrose resistant. The emulsion was partially added into a confection formula for soft candy preparation. As the replacement ratio of emulsions increased from 20% to 100%, the moisture, lutein content, and DPPH inhibition of soft candies increased by 61.98%, 325.55% and 135.66%, respectively, but hardness, chewiness, and resilience decreased by 61.68%, 67.81% and 47.76%, respectively, while color and sensory stabilities increased first, reaching the peaks at the level of 60%, and then decreased; however, the T g value first decreased and then increased. The emulsions that were filled evenly and stably in the jelly matrix enhanced the heat stability of the candies. This research provides an ingredient system for preparing sugar-resistant emulsions, which will be filling an unprecedented array of needs in confectionary development, such as the replacement of sugar and the delivery of fat-soluble bioactive compounds. Graphical abstract: Image 1 Highlights: Lutein-loaded emulsions were structured by 2.5% TPP particles and 0.5% XG as stabilizers. The emulsions were sucrose resistant and suitable for use in high sugar foods. The emulsions partially replace sugar making the soft candies healthier. The soft candies with strong antioxidant activity are low-sugar and lutein-rich.